Acute treatment of elderly patients with acetabular fractures by open reduction, internal fixation, and total hip arthroplasty: a 1–10-year follow-up of 48 patients - Ragnhild Loven Kirkeboe; Jan Erik Madsen; Lars Nordsletten; John Clarke-Jenssen (Acta Orthopaedica)
Background and purpose: Acetabular fractures in osteoporotic bone are associated with substantial joint impaction and comminution, previously shown to be prognostic for a poor result. A combined procedure of open reduction, internal fixation (ORIF), and total hip arthroplasty (THA) can be a good option, allowing for immediate weightbearing as tolerated. We report short- to medium-term outcome and complications of the results of patients treated with this combined procedure. Methods: 48 cases treated with ORIF and acute THA from 2000 to 2019 were identified from our local pelvic fracture registry, from which follow-up data was extracted. Descriptive statistics were used and Kaplan–Meier survival curves were calculated. Primary outcome was HHS at 1 year. Secondary outcomes were implant survival, complications requiring surgery, and mortality at 3 months. Results: There were 37 men and 11 women treated in the study period. Mean age was 68 (37–87) years. 6 patients died within 3 months of surgery, leaving 42 cases available for follow-up. Mean follow-up (FU) was 2.8 (1–16) years. The most common mechanism of injury was fall from standing height (n = 36). Medical comorbidities were common. Mean Harris Hip Score (HHS) was 83 (51–100) at 1-year follow-up. There were 7 reoperations: 6 for postoperative infection and 1 closed reduction of implant dislocation. 38 had their implant intact at latest FU. At the latest FU, 28 patients were ambulatory without a walking aid. Conclusion: Our results indicate that ORIF and acute THA can be performed with good functional results in patients with unreconstructable displaced acetabular fractures, but with a significant risk of infection and revision.